A Miniature Four-Channel Ion Trap Array Based on Non-silicon MEMS Technology - Qi Zhang; Xichi Lu; Ting Chen; Yu Xiao; Rujiao Yao; Jinyuan Yao (Micromachines, 2021)
With the increasing application field, a higher requirement is put forward for the mass spectrometer. The reduction in size will inevitably cause a loss of precision; therefore, it is necessary to develop a high-performance miniature mass spectrometer. Based on the researches of rectangular ion trap, the relationship between mass resolution and structural parameters of the ion trap array was analyzed by further simulation. The results indicate that, considering the balance of mass resolution and extraction efficiency, the preferable values for the field radius of exit direction y0 and ion exit slot width s0 are 1.61 mm and 200 μm, respectively. Afterwards, a miniature four-channel ion trap array (MFITA) was fabricated, by using MEMS and laser etching technology, and mass spectrometry experiments were carried out to demonstrate its performance. The mass resolution of butyl diacetate with m/z = 230 can reach 324. In addition, the consistency of four channels is verified within the error tolerance, by analyzing air samples. Our work can prove the correctness of the structural design and the feasibility of MEMS preparation for MFITA, which will bring meaningful guidance for its future development and optimization.